Alternative eyrie use in peregrine falcons: is it a female choice?. (4th February 2015) - Zuberogoitia, I.; Zabala, J.; Martínez, J. E.; Olsen, J.
Abstract All animals face the decision of where to breed, a decision that exerts a strong impact on fitness. We examined changes in choice of nest site in peregrine falcons (Falco peregrinus) over a 17‐year period in northern Spain. Falcons had a mean of 3.1 eyries per territory, each location used for a mean of 3.0 consecutive years. Surprisingly, change in eyrie location was not predicted by breeding productivity. However, breeding success decreased with the number of consecutive years that eyries were reused. Ectoparasitic infestation was not a significant predictor in the models. The number of fledglings in the previous season was the main factor explaining the eyrie‐switching decision, with successful pairs being more prone to move. Newly established females showed a higher tendency to switch (59%) than older territorial females (38%) but males did not exhibit the same tendency. High rainfall in April had a negative effect on productivity. In the case of females, changing the eyrie from one season to the next had a positive effect on productivity. In the case of models run with males as a random factor, rainfall in April and eyrie shelter reached significance. So, contrary to the 'win–stay, lose–switch' rule and in direct contrast with general literature, peregrines changed eyries after successfully raising large broods and eyrie switching increased the breeding success of females but not of males.